Malassezia Yeasts in Veterinary Dermatology: An Updated Overview - Guillot, Jacques; Bond, Ross (Frontiers in Cellular and Infection Microbiology, 2020)
Lipophilic yeasts of the genus Malassezia are important skin commensals and opportunistic skin pathogens in a variety of animals. The species M. pachydermatis was first isolated from the skin of a captive Indian rhinoceros with an exfoliative dermatitis in 1925, recognized as an important otic pathogen of dogs in the 1950's, and finally accepted, after several years of controversy, as a common cause of canine dermatitis in the 1990's. Since then, there has been considerable research into the biology of Malassezia yeasts and their interaction with their animal hosts. In dogs and cats, M. pachydermatis is associated with ceruminous otitis externa and a “seborrhoeic” dermatitis, wherein pruritic, erythematous skin lesions, often with brown/black greasy, malodourous material matting hairs, preferentially develop in intertriginous areas. Skin disease is favored by folds, underlying hypersensitivity disorders, endocrinopathies, defects of cornification, and in cats, various visceral paraneoplastic syndromes. Diagnosis is based on detecting the yeast in compatible skin lesions, usually by cytology, and observing a clinical and mycological response to therapy. Treatment normally comprises topical or systemic azole therapy, often with miconazole—chlorhexidine shampoos or oral itraconazole or ketoconazole. Management of concurrent diseases is important to minimize relapses. Historically, wild-type Malassezia isolates from dogs and cats were typically susceptible to azoles, with the exception of fluconazole, but emerging azole resistance in field strains has recently been associated with either mutations or quadruplication of the ERG11 gene. These observations have prompted increased interest in alternative topical antifungal drugs, such as chlorhexidine, and various essential oils. Further clinical trials are awaited with interest.